High-temperature-resistant low-expansion magnesium phosphate cement

By adding an appropriate amount of mineral blending to magnesium phosphate cement and adjusting the component ratio, the problem of unstable volume at high temperatures is solved, and the effect of resistance to high temperature and low expansion is achieved, and it is suitable for a variety of high temperature applications.

CN119898975APending Publication Date: 2025-04-29ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510063167.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing magnesium phosphate cement is unstable in high temperature environments, resulting in shrinkage and reduced strength, limiting its use in high temperature applications.

Method used

By adding magnesium-containing components, phosphates, retarders and mineral blends to magnesium phosphate cement, the proportion of components and mineral blends are adjusted to form magnesium phosphate cement that is resistant to high temperature and low expansion.

Benefits of technology

It significantly improves the volume stability and strength of magnesium phosphate cement at high temperatures, avoids the problem of drastic volume changes at high temperatures, and is suitable for applications such as fire-resistant coatings and high-temperature kilns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898975A_ABST
    Figure CN119898975A_ABST
Patent Text Reader

Abstract

The invention discloses high-temperature-resistant low-expansion magnesium phosphate cement which is prepared by mixing a solid component and water, the solid component comprises a magnesium-containing component, phosphate, a retarder and a mineral admixture, and the water-solid ratio is 0.2-2; the addition amount of the magnesium-containing component accounts for at least 30% of the total mass of the solid component according to the mass percent; the addition amount of the phosphate accounts for 25%-100% of the mass of the magnesium-containing component; the addition amount of the retarder accounts for 3-20% of the mass of the magnesium-containing component; the mass ratio of the mineral admixture to the magnesium-containing component is 0.2-1, and the mineral admixture is one or a mixture of any two or more of aluminum oxide, bauxite, blast furnace slag, fly ash and kaolin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic materials, and in particular to high-temperature resistant and low-expansion magnesium phosphate cement. Background Art

[0002] Magnesium phosphate cement (MPC) is a chemically bonded phosphate ceramic material, mainly composed of dead-burned magnesium oxide, phosphate solution and retarder. Through the acid-base reaction between magnesium oxide and phosphate, a reaction product with struvite (MgNH4PO4·6H2O) as the main component is formed. MPC is known for its fast curing, high early strength, low shrinkage and good bonding properties, which makes it an ideal choice for the rapid repair of damaged infrastructure. In addition, with the deepening of research and the development of technology, the application scope of MPC has been expanded to fields such as fire-retardant coatings, refractory castables and high-temperature kilns, which have strict requirements on the volume stability of the material at high temperatures.

[0003] However, MPC does not perform well in high temperature environments. Specifically, at around 100°C, MPC decomposes with about 20% mass loss and 2% linear shrinkage; between 200 and 800°C, its strength and volume further decrease due to crystal structure transformation. When the temperature rises to 1300°C, MPC undergoes a significant sintering process, resulting in more than 10% linear shrinkage and a sharp increase in strength. This thermal instability is the main obstacle limiting the application of MPC in high temperature environments.

[0004] In order to solve the problem of volume stability of MPC at high temperature, the existing technology has taken a variety of measures:

[0005] Inert filler addition: By adding inert fillers such as wollastonite or fly ash to MPC, the binder content and hydration products are reduced, thereby reducing the shrinkage caused by dehydration. Although this method can alleviate the shrinkage at low temperatures to a certain extent, at higher temperatures, the sintering effect of MPC will still cause drastic changes in volume, and the improvement effect is limited.

[0006] Reduce the amount of retarder: Reducing the use of retarders such as borax can increase the sintering temperature of MPC, thereby improving its volume stability. However, this only increases the temperature point at which sintering occurs, and does not solve the volume shrinkage problem caused by sintering itself.

[0007] Mineral admixtures: Adding 50% fly ash or abrasive blast furnace slag can effectively reduce the thermal expansion coefficient of MPC to 3% at 1200°C, thanks to the reaction of MPC with aluminosilicate minerals to form stable compounds such as KAlSi2O6 and KAlSiO4. The addition of sulphoaluminate cement can also improve the volume stability of MPC to a certain extent. For example, at 1100°C, the linear shrinkage can be reduced from 6% to 4%. Despite this, these methods still fail to completely eliminate the shrinkage problem of MPC at high temperatures. When the temperature is further increased, especially after 1200°C, magnesium phosphate cement will still experience drastic volume changes, and ultimately cannot fully meet the needs of practical engineering applications. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a high temperature resistant and low expansion magnesium phosphate cement to solve the problem of large shrinkage of the prior art magnesium phosphate cement at high temperatures.

[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0010] A high temperature resistant low expansion magnesium phosphate cement, the magnesium phosphate cement is prepared by mixing solid components and water: wherein the solid components include magnesium-containing components, phosphates, retarders and mineral admixtures, and the water-solid ratio is 0.2-2;

[0011] Calculated by mass percentage, the amount of the magnesium-containing component added accounts for at least 30% of the total mass of the solid component;

[0012] The amount of the phosphate added is 25% to 100% of the mass of the magnesium-containing component;

[0013] The amount of the retarder added is 3% to 20% of the mass of the magnesium-containing component;

[0014] The mass ratio of the mineral admixture to the magnesium-containing component is 0.2-1, and the mineral admixture is one of alumina, bauxite, blast furnace slag, fly ash and kaolin, or a mixture of any two or more thereof.

[0015] Preferably, the magnesium-containing component is dead-burned magnesium oxide, light-burned magnesium oxide or magnesium hydroxide, or a mixture of several of them.

[0016] Preferably, the particle size of the magnesium-containing component is less than 80 μm.

[0017] Preferably, the mass ratio of the magnesium-containing component to the phosphate is 2-6.

[0018] Preferably, the phosphate is one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, aluminum dihydrogen phosphate, zinc dihydrogen phosphate, or a mixture of any two or more thereof.

[0019] Preferably, the retarder is one of borax, boric acid or sodium tripolyphosphate, or a mixture of any two or more thereof.

[0020] Preferably, the mass ratio of the retarder to the magnesium-containing component is 0.06.

[0021] The present invention also provides an application of high temperature resistant low expansion magnesium phosphate cement, wherein the magnesium phosphate cement is used for fire retardant coating.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention proposes for the first time a magnesium phosphate cement having high temperature resistance and low expansion, and adopts a magnesium-containing component to react with phosphate to generate struvite, so that the magnesium phosphate cement has the advantages of fast hardening and early strength, good volume stability, no collapse at high temperature and being able to maintain a certain strength. When the magnesium phosphate cement of the present invention is used as an inorganic coating, the formed coating can be more firmly bonded to the protected substrate, and can better meet the requirements of being used as a coating.

[0024] 2. The present invention not only reduces the cementitious material component in the hardened body, but also reduces the shrinkage caused by the decomposition of hydration products by adding aluminum-containing mineral admixtures to the magnesium phosphate cement; in addition, the magnesium oxide in the magnesium phosphate cement can react with the mineral admixture at high temperature, and the expansion produced by the reaction offsets the shrinkage of the magnesium phosphate cement at high temperature, and finally makes the magnesium phosphate cement have no shrinkage at high temperature, thereby solving the problem of drastic volume change of the magnesium phosphate cement at a high temperature of 1300°C.

[0025] 3. The present invention not only reduces the cost of magnesium phosphate cement, but also significantly improves the volume stability of magnesium phosphate cement at high temperatures; at the same time, the coating of the present invention has a wide range of application scenarios, and can not only be used to prepare fire-retardant coatings, but also can be used in other high-temperature conditions such as high-temperature kilns, and can be targeted according to the high-temperature deformation requirements of the protective substrate. Proportion design. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Graph showing the thermal expansion coefficients of the MPCs prepared in Comparative Example 1 and Examples 3, 7 and 8 after testing. DETAILED DESCRIPTION

[0027] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.

[0028] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0029] 1. A high temperature resistant low expansion magnesium phosphate cement

[0030] The magnesium phosphate cement of the present invention is prepared by mixing solid components and water: wherein the solid components include magnesium-containing components, phosphates, retarders and mineral admixtures, and the water-solid ratio is 0.2-2; calculated by mass percentage, the addition amount of the magnesium-containing components accounts for at least 30% of the total mass of the solid components; the addition amount of the phosphates accounts for 25%-100% of the mass of the magnesium-containing components; the addition amount of the retarder accounts for 3%-20% of the mass of the magnesium-containing components; the mass ratio of the mineral admixture to the magnesium-containing components is 0.2-1, and the mineral admixture is one or a mixture of any two or more of alumina, bauxite, blast furnace slag, fly ash and kaolin.

[0031] Based on the prior art, the present invention conducts an in-depth study on the volume stability of magnesium phosphate cement at high temperatures, and unexpectedly finds that different types of mineral admixtures and different dosage ratios will change the microstructure of MPC, thereby affecting its important properties such as strength, durability and thermal stability. Under conditions below 1000°C, by selecting the type and dosage of mineral admixtures, the linear shrinkage of magnesium phosphate cement can be controlled within a lower range, or even within an extremely low range. Under conditions exceeding 1200°C, this adjustment can even cause a slight expansion of magnesium phosphate cement, and more importantly, this volume change does not cause cracking or peeling of magnesium phosphate cement, which shows that the magnesium phosphate cement described in the present invention can adjust its components according to actual application requirements, thereby controlling and adjusting the degree of volume change of magnesium phosphate cement under high temperature conditions; at the same time, it can also adapt to higher temperature environments and maintain sufficient strength in such environments. From the perspective of fire resistance, this is a completely unexpected discovery.

[0032] In some embodiments of the present invention, the mass ratio of the mineral admixture to the magnesium-containing component is 0.2 to 1, and the mineral admixture is one or a mixture of any two or more of alumina, bauxite, blast furnace slag, fly ash and kaolin. Among them, alumina is α-type alumina. The mineral admixtures all contain Al2O3, and different amounts of mineral admixtures added have a very significant effect on the volume stability of MPC. When the temperature gradually increases, the volume change of MPC decreases with the increase in the amount of mineral admixture. This is because struvite (MgNH4PO4·6H2O), one of the hydration products of MPC, loses six bound water molecules at around 100°C, and the dehydrated product MgKPO4 undergoes a crystal transformation between 400 and 600°C, which makes the volume change of MPC gradually decrease during the temperature change process of 100 to 600°C. At 800 to 1000°C, the volume of MPC remains almost unchanged because the high-temperature product MgKPO4 is stable within this temperature range. However, when the temperature rises to 1100°C, the volume change of MPC with a mineral admixture content of more than 40% decreases, while the MPC with a mineral admixture content of less than 40% shows a sharp increase in shrinkage, which indicates that some phase change reactions occur in the mineral admixture between 1000 and 1100°C, resulting in differences in the volume change of MPC with different contents of mineral admixtures. As the temperature continues to rise to 1300°C, the shrinkage of MPC increases significantly, especially for pure MPC (without mineral admixtures), which has a higher degree of sintering and a shrinkage of more than 15%. The volume change of magnesium phosphate cement described in the present invention shows a significant decreasing trend compared to pure MPC. In particular, as the amount of mineral admixtures increases, the hydration products generated in the mixed MPC gradually decrease, so the shrinkage of MPC caused by the decomposition of struvite also decreases as the amount of mineral admixtures increases. When the mass ratio of the mineral admixture to the magnesium-containing component reaches 0.8, at 1300°C, the magnesium phosphate cement even expands to a certain extent, and its internal structure has adapted to the high temperature environment. The decomposition of hydration products and the formation of new phases make the structure of magnesium phosphate cement more stable. Even in subsequent thermal cycles, no significant stress accumulation will occur inside the magnesium phosphate cement, thereby maintaining good volume stability and mechanical strength. Therefore, the mass ratio of the mineral admixture to the magnesium-containing component can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the implementation scheme, any of the above ranges can be combined with any other ranges.

[0033] In some embodiments of the present invention, the amount of magnesium-containing components added is at least 30% of the total mass of the solid components, calculated by mass percentage. A sufficient amount of magnesium-containing components can better ensure the formation of a sufficient amount of struvite phase, which is beneficial to improving the overall bonding performance of magnesium phosphate cement, and less than this amount will cause magnesium phosphate cement to be difficult to form sufficient strength in a short period of time. Therefore, calculated by mass percentage, the amount of magnesium-containing components added is at least 30% of the total mass of the solid components, preferably more than 35%, preferably more than 40%, and can be 30%, 35%, 40%, 50%, 55%, etc., and all ranges and sub-ranges between the above values. The magnesium-containing component is a mixture of one or more of dead-burned magnesium oxide, light-burned magnesium oxide or magnesium hydroxide, and the particle size of the magnesium-containing component is less than 80 μm, and more preferably less than 75 μm, which means that these powders are fine enough to help improve the reaction activity and promote full contact with other components. Heavy burned magnesium oxide, light burned magnesium oxide and magnesium hydroxide can provide magnesium oxide components for the reaction. When the magnesium-containing components are mixed, these materials can be mixed in any proportion, which can also make magnesium phosphate cement achieve the effect of high temperature resistance and low expansion.

[0034] In some embodiments of the present invention, the phosphate is one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, aluminum dihydrogen phosphate, zinc dihydrogen phosphate, or a mixture of any two or more thereof. The amount of the phosphate added is 25% to 100% of the mass of the magnesium-containing component. These phosphates have high reactivity and can react rapidly when in contact with magnesium oxide, so that the magnesium phosphate cement obtains sufficient mechanical properties and remains stable under high temperature conditions. Therefore, the amount of phosphate added can be 25%, 30%, 35%, 40%, 45%, 50%, 60%, 80%, 90%, 100%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0035] In some embodiments of the present invention, the retarder is one of borax, boric acid or sodium tripolyphosphate or a mixture of any two or more thereof, so as to ensure that the prepared slurry and paste can meet the requirements of the construction time. Therefore, according to the mass percentage, the amount of the retarder added accounts for 3% to 20% of the mass of the magnesium-containing component, which can be 3%, 5%, 6%, 10%, 15%, 20%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0036] 2. Examples and Comparative Examples

[0037] Example 1

[0038] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and bauxite are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of bauxite to magnesium oxide is 20%, and the water-solid ratio is 0.2.

[0039] Example 2

[0040] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and bauxite are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of bauxite to magnesium oxide is 60%, and the water-solid ratio is 0.2.

[0041] Example 3

[0042] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and bauxite are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of bauxite to magnesium oxide is 100%, and the water-solid ratio is 0.2.

[0043] Example 4

[0044] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and bauxite are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of bauxite to magnesium oxide is 100%, and the water-solid ratio is 0.4.

[0045] Example 5

[0046] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and bauxite are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 2, B / M is 0.06, the mass ratio of bauxite to magnesium oxide is 100%, and the water-solid ratio is 0.2.

[0047] Example 6

[0048] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and bauxite are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 6, B / M is 0.06, the mass ratio of bauxite to magnesium oxide is 100%, and the water-solid ratio is 0.2.

[0049] Example 7

[0050] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and metakaolin are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of metakaolin to magnesium oxide is 100%, and the water-solid ratio is 0.2.

[0051] Example 8

[0052] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and α-Al2O3 are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of α-Al2O3 to magnesium oxide is 100%, and the water-solid ratio is 0.2.

[0053] Example 9

[0054] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and blast furnace slag are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of blast furnace slag to magnesium oxide is 100%, and the water-solid ratio is 0.2.

[0055] Example 10

[0056] The dead-burned magnesium oxide, potassium dihydrogen phosphate, borax and fly ash are mixed evenly, and water is added and stirred evenly to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, the mass ratio of fly ash to magnesium oxide is 100%, and the water-solid ratio is 0.2.

[0057] Comparative Example 1

[0058] The dead-burned magnesium oxide, potassium dihydrogen phosphate and borax are uniformly mixed, and water is added and stirred to obtain magnesium phosphate cement, wherein M / P is 4, B / M is 0.06, and the water-solid ratio is 0.2.

[0059] The examples and comparative examples were processed according to the following method to obtain the samples:

[0060] Magnesium oxide, phosphate, borax and mineral admixtures were first premixed for 60 seconds, and then mixed for 180 seconds after adding water. The resulting uniform MPC slurry was used to prepare the test samples. All samples were cured for 28 days at a temperature of 20±1°C and a relative humidity of 55±5% before the performance test was performed.

[0061] 3. Performance Test

[0062] 1. Line shrinkage test

[0063] At least two rectangular samples (20 mm × 20 mm × 170 mm) were prepared, and the original length L0 of the sample was measured with a micrometer at room temperature. The sample was kept at the test temperature for 2 hours, cooled naturally to ambient temperature, and then the length L1 after the test was detected and recorded. The linear shrinkage L of the MPC sample was calculated based on the results before and after high temperature exposure. c , the formula is as follows:

[0064] L c =(L0-L1) / L0×100%

[0065] 2. Thermal expansion coefficient test

[0066] The thermal expansion coefficient of MPC was tested in the range of 20 to 1300 °C using a Netzsch DIL 402C dilatometer. In order to avoid adhesion of the molten MPC to the experimental instrument, the study was terminated when the shrinkage of MPC increased sharply. The heating rate was set to 10 °C / min, the horizontal constant load was set to 5N, and the linear change of size ΔL was recorded as a function of temperature and percentage of the initial length l. Before testing, the samples were dried in an oven at 40 °C for 1 day. The samples were cylindrical with a diameter of 5 ± 0.1 mm and a length of 3 ± 0.2 mm.

[0067] 4. Performance Comparison

[0068] The volume stability of the magnesium phosphate cements prepared in Examples 1 to 10 and Comparative Example 1 was tested, and the results are shown in Table 1.

[0069] Table 1 Linear shrinkage of MPC after treatment at different temperatures (%)

[0070]

[0071]

[0072] The thermal expansion coefficients of the MPCs prepared in Comparative Example 1 and Examples 3, 7 and 8 were tested. The results are as follows: Figure 1 shown.

[0073] Through the analysis of the above test results, we can see that:

[0074] (1) As can be seen from Table 1, Examples 1 to 7 are the results of the volume stability of magnesium phosphate cement doped with bauxite at high temperatures. As the test temperature increases, the linear shrinkage of Example 1 gradually increases, while the linear shrinkage of Examples 2-6 first decreases and then increases. According to the results of Examples 1 to 3, with the addition of bauxite, the linear shrinkage of MPC after high temperature is greatly reduced, and the greater the amount of bauxite added, the smaller the linear shrinkage of MPC doped with bauxite. This shows that the addition of mineral admixtures greatly reduces the linear shrinkage of MPC at high temperatures. Comparing the test results of Examples 3, 5 and 6, when the type and amount of mineral admixtures are the same, the high magnesium-phosphorus ratio MPC has better volume stability at high temperatures, which is related to the high volume stability of magnesium oxide and the amount of hydration products generated by the high magnesium-phosphorus ratio MPC.

[0075] (2) Examples 7 to 10 are magnesium phosphate cements mixed with different types of mineral admixtures. As the test temperature increases from 800°C to 1100°C, the linear shrinkage of magnesium phosphate cement decreases significantly. As the temperature increases from 1100°C to 1300°C, the linear shrinkage of magnesium phosphate cement tends to increase, while the linear shrinkage of Example 8 tends to continue to decrease, and even expands by 0.89% after 1300°C. It can be seen that although the amount of mineral admixtures is consistent, the type of mineral admixture has a greater impact on the volume stability of magnesium phosphate cement at high temperatures, but the volume stability is better than that of Comparative Example 1.

[0076] (3) Considering the real-time length change of magnesium phosphate cement specimens with temperature change, magnesium phosphate cement comparative example 1 and embodiments 3, 7 and 8 were made into thermal expansion specimens, and the length change of the specimens with temperature was tested using a thermal expansion coefficient measuring instrument according to the specification. The results are as follows Figure 1 Compared with the test results of the volume stability of magnesium phosphate cement at room temperature in Table 1, Figure 1 Comparative Example 1 shows a large shrinkage at high temperature, while the shrinkage of Examples 3, 7 and 8 is less than that of Comparative Example 1, and Example 8 shows a certain expansion at 1200° C. The test results of the thermal expansion coefficient determination are consistent with the test results of the volume stability of magnesium phosphate cement at room temperature. It can be seen that the addition of mineral admixtures can greatly improve the volume stability of magnesium phosphate cement at high temperatures, and even the addition of appropriate types of mineral admixtures can prevent magnesium phosphate cement from shrinking at high temperatures.

[0077] (4) Example 8 exhibited a certain degree of expansion under the condition of temperature exceeding 1200°C. After further observation of the sample of Example 8, it was unexpectedly found that although Example 8 showed slight expansion, the sample of Example 8 did not crack or peel off, and still had a certain strength. This was a surprising discovery, which showed that magnesium phosphate cement using α-Al2O3 as a mineral admixture could show better stability under high temperature (over 1200°C) conditions, especially from the perspective of fire resistance, such improvement was very beneficial and unexpected.

[0078] (5) Compared with other embodiments and comparative examples, the alumina in the α-Al2O3 used in the present invention has high purity, which can react with the magnesium oxide in the magnesium phosphate cement to form magnesium aluminum spinel and then expand, reducing or even compensating for the shrinkage caused by the high-temperature sintering of the magnesium phosphate cement; while the admixtures in other embodiments contain part of silica in addition to alumina, which reacts with magnesium oxide at high temperature to form magnesium silicate, resulting in shrinkage, and its contribution to the volume stability at high temperature is not as good as that of α-Al2O3; therefore, embodiment 8 incorporating high-purity α-Al2O3 exhibits better high-temperature volume stability among many embodiments. At the same time, embodiments 1 to 8 also show that the content of alumina in the admixture and the amount of the admixture can be adjusted according to the requirements of high-temperature volume stability, so as to adjust the volume stability of the magnesium phosphate cement at high temperature.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A high temperature resistant low expansion magnesium phosphate cement, characterized in that: The magnesium phosphate cement is prepared by mixing solid components and water: wherein the solid components include magnesium-containing components, phosphates, retarders and mineral admixtures, and the water-solid ratio is 0.2-2; Calculated by mass percentage, the amount of the magnesium-containing component added accounts for at least 30% of the total mass of the solid component; The amount of the phosphate added is 25% to 100% of the mass of the magnesium-containing component; The amount of the retarder added is 3% to 20% of the mass of the magnesium-containing component; The mass ratio of the mineral admixture to the magnesium-containing component is 0.2-1, and the mineral admixture is one of alumina, bauxite, blast furnace slag, fly ash and kaolin, or a mixture of any two or more thereof.

2. The magnesium phosphate cement according to claim 1, characterized in that: The magnesium-containing component is one or a mixture of dead-burned magnesium oxide, light-burned magnesium oxide or magnesium hydroxide.

3. The magnesium phosphate cement according to claim 2, characterized in that: The particle size of the magnesium-containing component is less than 80 μm.

4. The magnesium phosphate cement according to claim 2, characterized in that: The mass ratio of the magnesium-containing component to the phosphate is 2-6.

5. The magnesium phosphate cement according to claim 2, characterized in that: The phosphate is one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, aluminum dihydrogen phosphate, zinc dihydrogen phosphate, or a mixture of any two or more thereof.

6. The magnesium phosphate cement according to claim 2, characterized in that: The retarder is one of borax, boric acid or sodium tripolyphosphate or a mixture of any two or more thereof.

7. The magnesium phosphate cement according to claim 5, characterized in that: The mass ratio of the retarder to the magnesium-containing component is 0.

06.

8. An application of high temperature resistant low expansion magnesium phosphate cement, characterized in that: The magnesium phosphate cement described in any of claims 1 to 7 is used for fire retardant coating.